Randomized crossover trial of a pressure sensing visual feedback system to improve mask fitting in noninvasive ventilation. - Brill,A-K; Moghal,M; Morrell,MJ; Simonds,AK (Respirology, 2017)
BACKGROUND AND OBJECTIVE: A good mask fit, avoiding air leaks and pressure effects on the skin are key elements for a successful noninvasive ventilation (NIV). However, delivering practical training for NIV is challenging, and it takes time to build experience and competency. This study investigated whether a pressure sensing system with real-time visual feedback improved mask fitting. METHODS: During an NIV training session, 30 healthcare professionals (14 trained in mask fitting and 16 untrained) performed two mask fittings on the same healthy volunteer in a randomized order: one using standard mask-fitting procedures and one with additional visual feedback on mask pressure on the nasal bridge. Participants were required to achieve a mask fit with low mask pressure and minimal air leak (<10 L/min). Pressure exerted on the nasal bridge, perceived comfort of mask fit and staff- confidence were measured. RESULTS: Compared with standard mask fitting, a lower pressure was exerted on the nasal bridge using the feedback system (71.1 ± 17.6 mm Hg vs 63.2 ± 14.6 mm Hg, P < 0.001). Both untrained and trained healthcare professionals were able to reduce the pressure on the nasal bridge (74.5 ± 21.2 mm Hg vs 66.1 ± 17.4 mm Hg, P = 0.023 and 67 ± 12.1 mm Hg vs 60 ± 10.6 mm Hg, P = 0.002, respectively) using the feedback system and self-rated confidence increased in the untrained group. CONCLUSION: Real-time visual feedback using pressure sensing technology supported healthcare professionals during mask-fitting training, resulted in a lower pressure on the skin and better mask fit for the volunteer, with increased staff confidence.